Fire in the Canyon : Religion, Migration, and the Mexican Dream - Sarat, Leah (Book collections on Project MUSE., 2013)
The canyon in central Mexico was ablaze with torches as hundreds of people filed in. So palpable was their shared shock and grief, they later said, that neither pastor nor priest was needed. The event was a memorial service for one of their own who had died during an attempted border passage. Months later a survivor emerged from a coma to tell his story. The accident had provoked a near-death encounter with God that prompted his conversion to Pentecostalism. Today, over half of the local residents of El Alberto, a town in central Mexico, are Pentecostal. Submitting themselves to the authority of a God for whom there are no borders, these Pentecostals today both embrace migration as their right while also praying that their "Mexican Dream"--The dream of a Mexican future with ample employment for all - will one day become a reality. This book provides a look at the dynamic relationship between religion, migration, and ethnicity across the U.S.-Mexican border